Early- and later-life stimulation: How retirement shapes the effect of education on old-age cognitive abilities - Hendrik Schmitz; Matthias Westphal (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
We study the interaction of education in adolescence and labor force participation around retirement age and its effect on cognitive abilities for individuals in Europe. Besides a direct long-run effect of education, indirect ones may arise, specifically through labor force participation. We suggest an estimator for causal mediation analysis that accommodates endogeneity and heterogeneous treatment effects and use it to identify indirect effects within the education effect. We find that education raises cognitive abilities by about 8 percent. Among the more educated, labor force participation accounts for 36 percent of the total effect, emphasizing important complementarities between education and labor force participation. – – Wir untersuchen die Wechselwirkung zwischen der Bildung in der Jugend und der Beteiligung am Erwerbsleben im Rentenalter und ihre Auswirkungen auf die kognitiven Fähigkeiten von Personen in Europa. Neben einem direkten langfristigen Effekt der Bildung können indirekte Effekte auftreten, insbesondere durch die Erwerbsbeteiligung. Wir schlagen einen Schätzer für die kausale Mediationsanalyse vor, der Endogenität und heterogene Behandlungseffekte berücksichtigt und verwenden ihn zur Identifizierung indirekter Effekte innerhalb des Bildungseffekts. Es stellt sich heraus, dass Bildung die kognitiven Fähigkeiten um etwa 8 Prozent erhöht. Bei den höher Gebildeten ist die Erwerbsbeteiligung für 36 Prozent des Gesamteffekts verantwortlich. Dies unterstreicht die wichtigen Komplementaritäten zwischen Bildung und Erwerbsbeteiligung.
Keywords: C31; J14; J24; 330; Cognitive abilities; causal mediation analysis; marginal treatment effects; education